Food wars! : shokugeki no Soma. Volume 35, The divine tongue's despair - Tsukuda, Yuto, 1989- (Shonen Jump manga., 2020)
"Soma Yukihira's old man runs a small family restaurant in the less savory end of town. Aiming to one day surpass his father's culinary prowess, Soma hones his skills day in and day out until one day, out of the blue, his father decides to enroll Soma in a classy culinary school! Can Soma really cut it in a place that prides itself on a 10 percent graduation rate? And can he convince the beautiful, domineering heiress of the school that he belongs there at all?!... The Blue cooking competition rages on! Intent on getting his rematch with Asahi Saiba, Soma keeps racking up win after win, even against formidable noir opponents. Meanwhile, in the other tournament bracket, Erina faces a suspiciously heinous schedule. What exactly is the book master planning?"--Provided by publisher.